Mortuary Behavior and Social Trajectories in Pre- and Protopalatial Crete. - Herrero, Borja Legarra (Prehistory monographs., 2014)
"This study aims to reach a better understanding of a key period in Cretan and European history through a comprehensive study of the totality of the known Cretan mortuary record during the Pre- and Protopalatial periods (Early Minoan I to Middle Minoan IIB)"--